Improving the Efficiency of GF-120 Baits in Attracting BactroceraZonata by Adding Ammonium Compounds with Particular Emphasis on pH level - Mohamed Ghamin Nabil (International Journal of Entomology, 2018)
The peach fruit fly, Bactrocerazonata (Saunders) is a serious pest attacking a wide range of fruits. Field experiments were carried out, at Mansoura district, Dakahlia Governorate, Egypt to evaluate the efficiency of di- ammonium phosphate, ammonium carbonate and ammonium acetate in enhancing GF-120, as insecticidal bait, for B. zonata based on their pH level under high and low population levels of B. zonata. Results showed that di-ammonium phosphate enhanced the attractiveness of GF-120 the most, followed by ammonium carbonate and ammonium acetate. Without adding any of the ammonium compounds to the GF-120 bait, the bait attracted the fewest B. zonata flies regardless of population levels. As the concentrations of ammonium compounds increased, the pH-level increased as well in the prepared GF-120 solutions, resulting in increased numbers of B. zonata flies captured. In contrast to males, females of B. zonata were more responsive to increase concentrations of the three ammonium compounds tested. Accordingly, all treatments attracted females more than males. The sex ratio (as number of attracted females per one male) was generally higher under low than high fly population levels.
Keywords: Insects